The Local Product-Based Science and Science Learning and Generative AI: A Model for Strengthening Digital Literacy and Empowering MSMEs in Elementary Madrasahs - Iftha Nur Sutanti; Hidayaturrohmah Hidayaturrohmah; Donny Khoirul Azis (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
Science learning in Madrasah Ibtidaiyah is still dominated by textual and memorization approaches, resulting in low student engagement. This study aimed to describe the implementation of science learning based on local product observation through the use of generative artificial intelligence (AI) in creating promotional flyers in Grade V of MI Ma'arif NU 1 Cilongok. The study employed a qualitative descriptive approach involving 19 fifth-grade students. Data were collected through participatory observation, unstructured interviews, student observation reports, and promotional flyer artifacts, and were analyzed using the Miles and Huberman interactive model. The results showed that all students (100%) successfully completed the four learning stages, namely field observation, report writing, AI-assisted flyer creation, and publication through social media. Student engagement increased from 52.6% before implementation to 100% after the learning activities, accompanied by improvements in creativity and digital literacy. The most notable outcome was the establishment of a collaboration between the Kerupuk Lawas MSME and the Bunda Madani MSME, initiated through a promotional flyer created by the students. This study contributes to the development of an integrative IPAS learning model that combines contextual field observation, Project-Based Learning, and generative AI to strengthen digital literacy while fostering collaboration between schools and local communities. However, the findings should be interpreted within the context of this study, as the research involved only one fifth-grade classroom in a single elementary madrasah and was conducted over a relatively short implementation period.